Violence, Insecurity and Marginality in Pastoralist Spaces: The Horn of Africa and the Sahel Regions (The Strategic Review for Southern Africa, 2020)
The pastoral world is defined by the prevalence of war, various forms of insecurity and lack of development, which constitutes violence in all its forms: direct war violence, structural violence (emanating from economic alienation and marginalisation, political repression, poverty, destitution and climatic vulnerability) and cultural violence (bias towards and the securitisation of pastoralist economic and social system). In effect, in human security parlance, the violation of freedom from fear and freedom from want is prevalent that it appears inherent to the nature of the pastoral way of being. The pastoral way of life is considered as an ephemeral state of encroachment of modern nation-state institutions. Therefore, pastoralist-state relations have always been strained. Their precarious existence on the fringe of every state they form part of is consequently considered as normalcy for pastoralists until their livelihood, socio-economic and political system is transformed into the dominant socio-economic and political systems the states are built on. The pastorialist conception of their livelihood and the entirety of their view of 'good life' is denigrated and their voice silenced. By reflecting on the book entitledS in the Horn of Africa and the Sahel by the United Nations Economic Commission for Africa, this review article examines violence in pastoral society.